Arkoun's Reading Of The Qur'an (Semiotics) - Ahmad Zabidi; Sri Sunantri; Maulana (Jurnal Ilmu Sosial dan Humaniora, 2025)
The Quran is a book for humanity; it holds a sacred mythological significance in every message it conveys. The abundant symbolic language found in the Quran provides guidance to humanity. However, interpretations of the Quran have often seemed to ignore the depth of its meaning and instead follow prevailing ideologies. Understanding the Quran is not as easy as simply turning the palm of one's hand. The text of the Quran contains numerous meanings, beyond simply understanding the text's narrow meaning. This has been the goal, from ancient times to the present, of reading the Quran to uncover its hidden meanings. In the semiotic category, the Quranic text as parole is supplanted by the text as langue, so the Quran remains parole for believers. Langue is the totality of passively acquired habits taught by a language community, and parole is the sum of what people say and is the individual manifestation of language.